Crystal structure and interaction studies of human DHTKD1 provide insight into a mitochondrial megacomplex in lysine catabolism - Bezerra, Gustavo A.; Foster, William R.; Bailey, Henry J.; Hicks, Kevin G.; Sauer, Sven; Dimitrov, Bianca; McCorvie, Thomas J.; Okun, Jürgen G.; Rutter, Jared; Kölker, Stefan; Yue, Wyatt W. (IUCrJ, 2020)
DHTKD1 is a lesser-studied E1 enzyme among the family of 2-oxoacid dehydrogenases. In complex with E2 (dihydrolipoamide succinyltransferase, DLST) and E3 (dihydrolipoamide dehydrogenase, DLD) components, DHTKD1 is involved in lysine and tryptophan catabolism by catalysing the oxidative decarboxylation of 2-oxoadipate (2OA) in mitochondria. Here, the 1.9 angstrom resolution crystal structure of human DHTKD1 is solved in complex with the thiamine diphosphate co-factor. The structure reveals how the DHTKD1 active site is modelled upon the well characterized homologue 2-oxoglutarate (2OG) dehydrogenase but engineered specifically to accommodate its preference for the longer substrate of 2OA over 2OG. A 4.7 angstrom resolution reconstruction of the human DLST catalytic core is also generated by single-particle electron microscopy, revealing a 24-mer cubic scaffold for assembling DHTKD1 and DLD protomers into a megacomplex. It is further demonstrated that missense DHTKD1 variants causing the inborn error of 2-aminoadipic and 2-oxoadipic aciduria impact on the complex formation, either directly by disrupting the interaction with DLST, or indirectly through destabilizing the DHTKD1 protein. This study provides the starting framework for developing DHTKD1 modulators to probe the intricate mitochondrial energy metabolism.